Friedel Oscillations in graphene: Sublattice Asymmetry in Doping - Ferreira, Mauro; Power, Stephen (My University, 2013)
Symmetry breaking perturbations in an electronically conducting medium are known to produce Friedel oscillations in various physical quantities of an otherwise pristine material. Here we show in a mathematically transparent fashion that Friedel oscillations in graphene have a strong sublattice asymmetry. As a result, the presence of impurities and/or defects may impact the distinct graphene sublattices very differently. Furthermore, such an asymmetry can be used to explain the recent observations that nitrogen atoms and dimers are not randomly distributed in graphene but prefer to occupy one of its two distinct sublattices. We argue that this feature is not exclusive of nitrogen and that it can be seen with other substitutional dopants
PUBLISHED
Keywords: Physics; Nanoscience & Materials